Latrine Utilization and Its Associated Factors Among Community Led Total Sanitation Implemented and Non-Implemented Kebeles of Tullo District, West Hararge, Eastern Ethiopia - Mohammed Murad; Dinku Mekbib Ayele; Tesfaye Gobena; Fitsum Weldegebreal (SAGE Publishing, 2022)
Background: Improper human waste management is a major health problem in most developing countries, including Ethiopia. In Ethiopia, the majority of the population used unimproved sanitation facilities and practiced open defecation. This problem is significantly higher in the rural parts of the country. Objective: The aim of this study was to assess latrine utilization and associated factors among Community Led Total Sanitation (CLTS) implemented and non-implemented kebeles in Tullo District, West Hararghe, and Eastern Ethiopia. Methods: A community-based comparative cross-sectional study design was conducted in 740 households in 3 kebeles Community Led Total Sanitation implemented and 3 kebeles non-Community Lead Total Sanitation implemented for comparison. Study units were selected using a multi-stage sampling technique. The data was cleaned and coded before being entered into Epi-data version 3.1 and analyzed with the Statistical Package for the Social Sciences version 20. Logistic regression analysis was used to assess the association between dependent and independent variables. Result: In this study, the overall prevalence of latrine utilization in the study area was 415 (56.1%) (95% CI = 52.6%, 59.9%). Of them, 243 (65.7%) (95% CI = 60.4%, 70.3%) and 172 (46.5%) (95% CI = 41.3%, 51.7%) of participants in the CLTS and non CLTS kebeles were utilized latrine, respectively. In CLTS implemented kebeles, literate (AOR = 3.66; 95% CI: 1.53, 8.73), households being visited by health extension worker (AOR = 11.72; 95% CI: 4.01, 34.31), households being graduated as model family(AOR = 7.56, 95% CI: 2.79, 20.44), ⩾2 years by years of latrine owning (AOR = 12.10, 95% CI: 3.21, 45.64), >6 meters distance of toilet to home (AOR = 27.43, 95%CI: 8.43, 89.29),Latrine with hand washing (AOR = 2.93, 95%CI: 1.19, 7.17), latrine with superstructure (AOR = 6.54, 95% CI: 2.04, 20.98) were significantly associated with latrine utilization, while in non CLTS implemented kebeles, literate (AOR = 25.78, 95% CI: 13.35, 49.78), medium wealth status(AOR = 4.87, 95% CI: 2.10, 11.29), poor wealth status(AOR = 2.51, 95% CI: 1.26, 5.01) were significantly associated with latrine utilization. Conclusion: The findings of this study revealed that more of the rural households had utilized latrines in CLTS implemented kebeles than non-CLTS implemented' kebeles. So, it is recommended that the district health office increase the latrine utilization rate through the effective and sustainable implementation of the CLTS approach.